2018
DOI: 10.1080/10942912.2018.1437177
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior and stability of emulsions obtained from Pereskia aculeata Miller via different drying methods

Abstract: Hydrocolloid powders from Pereskia aculeata Miller were obtained by using drying in a vacuum oven and freeze-drying at different concentrations (0.5-3.0 g of hydrocolloids/100 g of aqueous phase) to produce oil-in-water emulsions. The rheological characteristics of the emulsions and their microstructures were determined. The freeze-dried hydrocolloids and higher hydrocolloid concentrations resulted in emulsions with higher viscosities. The drying method and hydrocolloid concentration influenced the thixotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
0
11
0
3
Order By: Relevance
“…In the third time interval, this interaction could form during low applied shear forces. Forming this internal structure at lower shear stress demonstrates high thixotropic behavior and recoverable character for the 3‐ITT test (Junqueira, Amaral, Leite Oliveira, Prado, & de Resende, 2018). Similar to the decrease in fat ratio, it is seen that the recovery characteristic can be regained by FOB with the reduction of the gum ratio.…”
Section: Resultsmentioning
confidence: 99%
“…In the third time interval, this interaction could form during low applied shear forces. Forming this internal structure at lower shear stress demonstrates high thixotropic behavior and recoverable character for the 3‐ITT test (Junqueira, Amaral, Leite Oliveira, Prado, & de Resende, 2018). Similar to the decrease in fat ratio, it is seen that the recovery characteristic can be regained by FOB with the reduction of the gum ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Após o preparo das emulsões foi realizada análise visual com uma pequena quantidade das amostras verificando a viscosidade, a formação de agregados e a textura através do tato (JUNQUEIRA et al, 2018).…”
Section: Análise Macroscópicaunclassified
“…As nanoemulsões apresentam tamanhos de gotículas com um diâmetro médio de 20 a 200 nm. Portanto, as emulsões estão presentes na escala manométrica, mais estáveis termodinamicamente e, por isso, possuem estabilidade maior que as microemulsões (JUNQUEIRA et al, 2018).…”
Section: Tamanho Das Partículasunclassified
See 1 more Smart Citation
“…Emulsions demonstrate non-Newtonian rheological behavior with apparent yield stress which can be fitted well by various models, for instance, Bingham, Herschel–Bulkley, power law, and Casson models [ 15 ]. Additionally, the thixotropic behavior of emulsions, which is a time-dependent rheology property, is also commonly described, in which the apparent viscosity decreases with increasing time (under a certain amount of shear stress) and the viscosity recovers when the emulsion is allowed to stand [ 16 ]. Therefore, these findings from reported studies suggested the importance of the aforementioned parameters in determining the emulsion stability and, thus, they must be thoroughly investigated, especially when new combinations or blends of oil are used as the dispersed phase, for instance, in developing a concentrated O/W emulsion, whereby the oil incorporation percentage is relatively high.…”
Section: Introductionmentioning
confidence: 99%